Mekanisme Penyidikan Tindak Pidana Manipulasi Data Transaksi Grab di Polres Lamongan - Muhammad Rizqy Romadhony (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2019)
The crime of manipulating transaction data that occurred in theLamongan police area is one form of the development of new crimes that canbe categorized as Cyber crimes. The existence of online transportation itselfactually has no legal rules governing, but all forms of transaction activitiesas stipulated in the Electronic Information and Transaction Law. So that inthe implementation of the investigation of cyber crime, this should also referto the provisions stipulated in the Electronic Information and TransactionAct. This type of research is field research by collecting data from its sourceand taking an empirical juridical approach. The results of the study showthat the investigation carried out by Lamongan Police investigators wascarried out as well as the usual criminal acts stipulated in the provisions ofthe Criminal Procedure Code. As stipulated in the Information andInformation Technology Law itself, the investigation is regulated inaccordance with the provisions of the Criminal Procedure Code and this Lawwhich also contains several special rules. The problem during theinvestigation is the limited number of investigators and the absence ofcooperation between the Police investigator and PPNS investigators so thatthe investigation cannot be carried out effectively